“They gave us the right to choose.” A qualitative study of preferences for differentiated service delivery location among recipients of antiretroviral therapy at Lighthouse Trust in Lilongwe Malawi - Lisa Orii; Kate S. Wilson; Jacqueline Huwa; Christine Kiruthu-Kamamia; Odala Sande; Agness Thawani; Astrid Berner-Rodoreda; Evelyn Viola; Hannock Tweya; Petros Tembo; Wapu Masambuka; Richard Anderson; et al. (PLoS ONE, 2025)
Some differentiated service delivery (DSD) models for antiretroviral therapy (ART) allow stable recipients of care (RoC) to receive multi-month ART drug refills and complete rapid reviews in community sites. As DSD options expand across sub-Saharan Africa, RoC’s preferences and perspectives on community-based DSD versus clinic-based care models warrants attention. Lighthouse Trust (LT) implements DSD services for the Ministry of Health in Lilongwe, Malawi, including a community-based ART service delivery model that complements it traditional, clinic-based care. In this qualitative study, we explore reasons why RoC enrolled in LT clinics and eligible for DSD chose clinic-based ART services or a Nurse-led Community-based ART Program (NCAP) that reaches clients in established community peer support groups. We conducted eight focus group discussions (FGDs) among LT RoC: four FGDs among NCAP groups and four clinic-based FGDs (2 per setting) to explore opinions, preferences, and perceptions about ART service delivery. FGDs were recorded in Chichewa, translated and transcribed into English for thematic analysis. Findings were discussed with LT and NCAP teams to ensure results resonated with their personal experiences. Sixty-three participants took part in FGDs. Many findings were similar across care model. Across both NCAP and clinic FGDs, RoC were pleased with the care quality and appreciated the convenience of integrating their appointment visits at their chosen care model into their daily lives. Across FGDs, RoC also appreciated the quality of care, the respectful provider-to-patient interactions, and the attention to privacy at community and clinic sites. RoC in both clinic and NCAP care models expressed satisfaction with their chosen care model and preferred that choice over alternative options and locations, some noting their willingness to travel far to access LT’s high quality of clinic-based care. Privacy protection was an important consideration for choosing care models. At LT clinics, RoC highlighted the importance of physical separation between LT’s HIV-specific service site and other care services. In NCAP, RoC expressed that their choice of care model was reinforced by the sense of mutual support they received through NCAP peer support. These findings suggest the importance of offering personal choice to RoC on care model and selection of DSD options to support their ongoing engagement in care.